The emerging roles and mechanisms of exosomal non-coding RNAs in the mutual regulation between adipose tissue and other related tissues in obesity and metabolic diseases - Pan, Shifeng; Chen, Yongfang; Yan, Jie; Li, Fei; Chen, Xinyu; Xu, Xingyu; Xing, Hua (Frontiers in Endocrinology, 2022)
Exosomes (EXs) are the major types of extracellular vesicles (EVs) of 30-100 nm diameter that can be secreted by most cells to the extracellular environment. EXs transport endogenous cargoes (proteins, lipids, RNAs, etc.) to target cells and thereby triggers the release of these bioactive components, which then play important roles in regulating numerous biological processes under both physiological and pathological conditions. Throughout the studies in recent years, growing evidences have shown that EXs-derived non-coding RNAs (EXs-ncRNAs) are emerging as key players in cell-to-cell communication between adipose tissue and other related tissues in obesity and metabolic diseases. In this review, we will summarize the recent findings about EXs-ncRNAs, especially focus on the following aspects: 1) the biogenesis of EXs and emerging roles of EXs-ncRNAs, 2) the role of EXs-ncRNAs (EXs-miRNAs, EXs-lncRNAs, EXs-circRNAs, etc.) that were secreted by adipose-related tissues in promoting the differentiation of preadipocytes into mature and fully functional adipocytes, and 3) the crosstalk between the adipose tissue derived EXs-ncRNAs and the development of insulin resistance, obesity and various cancers. This review aims to reveal the emerging roles and mechanisms of EXs-ncRNAs in the mutual regulation of adipose tissue and its related tissues in obesity and metabolic diseases, so as to provide references for elucidating the etiology of obesity and related metabolic diseases and screening novel therapeutic targets.